Comparative Analysis of Net Realizable Value and Replacement Costing–A Comment. - Nichols, Donald R. (The Accounting Review, 1973)
The article comments on a comparative analysis of net realizable value (NRV) and replacement costing, in reference to the article written by Norton M. Bedford and James C. McKeown for the April 1972 issue of the periodical "The Accounting Review." The author agrees that goal congruence aspects of alternative accounting procedures should be considered in evaluating their effectiveness. He also emphasizes the overstatement of the NRV model. However, this should not be interpreted as a criticism of the NRV model.